2023
DOI: 10.1007/s12144-023-04940-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of news media use and political discussions on social self-efficacy through sense of unity: an analysis of mediation model invariance with Spanish and Portuguese adolescents

Abstract: Discussing sociopolitical issues with family or friends during adolescence, as well as staying informed through media outlets, is key to developing active civic engagement for both youth and future adults. Likewise, these communicative exchanges promote a sense of belonging and social skills which foster adolescents’ wellbeing. This research aims to analyze the influence of participation in communication about political and social issues on adolescents’ social self-efficacy, both directly and as well as indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Once obtaining results on the scale's reliability and validity in Spanish and Portuguese adolescents, mean scores of both groups were examined, taking into consideration sex, age, and country. Results showed that Spanish adolescents score higher than Portuguese, coinciding with research by Salado et al (2023). However, we must be cautious when interpreting these results given that there is a noticeable lack of prior research comparing the social self-efficacy scale in both countries.…”
Section: Discussionsupporting
confidence: 61%
“…Once obtaining results on the scale's reliability and validity in Spanish and Portuguese adolescents, mean scores of both groups were examined, taking into consideration sex, age, and country. Results showed that Spanish adolescents score higher than Portuguese, coinciding with research by Salado et al (2023). However, we must be cautious when interpreting these results given that there is a noticeable lack of prior research comparing the social self-efficacy scale in both countries.…”
Section: Discussionsupporting
confidence: 61%